2009
DOI: 10.1152/ajplung.90596.2008
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic cell adhesion molecule 6 in human lung: regulated expression of a multifunctional type II cell protein

Abstract: It binds gram-negative bacteria and is overexpressed in cancers, where it is antiapoptotic and promotes metastases. To characterize CEACAM6 expression in developing lung, we cultured human fetal lung epithelial cells and examined responses to differentiation-promoting hormones, adenovirus expressing thyroid transcription factor-1 (TTF-1), and silencing of TTF-1 with small inhibitory RNA. Glucocorticoid and cAMP had additive stimulatory effects on CEACAM6 content, and combined treatment maximally increased tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 46 publications
11
39
0
Order By: Relevance
“…CEACAM6/CEA immunoreactivity has been reported for al- veolar epithelium of adult human lung (30,32), and previously we found that fetal human type II cells in monolayer culture expressed CEACAM6 (24). Fig.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…CEACAM6/CEA immunoreactivity has been reported for al- veolar epithelium of adult human lung (30,32), and previously we found that fetal human type II cells in monolayer culture expressed CEACAM6 (24). Fig.…”
Section: Resultssupporting
confidence: 63%
“…Results of our laboratory's previous studies (2,24) plus the data of Fig. 5, Be and Bg, establish the expression of CEACAM6 in type II cells of the alveolus.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations